The Effects of Implementing the Catalytic Agency Contract under Executive Decree 18-199 Related to Public Utility Delegations - Hafdallah, Abdellali; Ladjelat, Faouaz (Journal of Legal Studies and Researches, 2021)
After the fulfillment of the terms of the contract "incentive agency" enters into force, this contract will arrange for a set of effects against both the delegated authority and the authorized representative representing the goal of this research paper. The gravity of these means and the powers granted to the delegated authority is not arbitrary in exercising its powers, but a number of obligations were also approved for him.